Spiritual and human health: pedagogical aspect - Афонін, Анатолій; Дороніна, Тетяна (Pedagogy of Higher and Secondary Education, 2014)
Afonin A. P., Doronina T. A. Spiritual and human health: pedagogical aspect. The rapid deterioration in the health of today’s youth is of concern to both public and scientific community. Scientists and educators-practices, identifying adverse factors affecting the health of students, are not careful to spiritual health component, at that the activities which save their healthhave mainly information, preventive and healthful character. Spirituality is to be regarded as the core of a truly healthy person, which determines the need to create health pedagogy, pedagogical knowledge as a field aimed at the education of a person with a new understanding of the meaning of life, their relationship with nature and humanity; a man ready to face the challenges of modernity.